2011
DOI: 10.1136/amiajnl-2011-000199
|View full text |Cite
|
Sign up to set email alerts
|

Making electronic prescribing alerts more effective: scenario-based experimental study in junior doctors

Abstract: Both kinds of e-prescribing alerts significantly reduced prescribing error rates, but modal alerts were over three times more effective than non-modal alerts. This study provides new evidence about the relative effects of modal and non-modal alerts on prescribing outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 33 publications
1
48
0
Order By: Relevance
“…Other approaches could be possible as well. For example, we rigorously avoided the forcing function approach, but that approach has shown benefit in studies of medication safety prompting systems 24,25 even though it also leads to high override rates. 26 As another example, a recent Cochrane review 1 found that computer-generated reminders delivered on paper were effective in changing practice and that providing space for physicians to respond led to greater effect size; including an explanation of the reminder, however, which we avoided, also improved effect size.…”
Section: Discussionmentioning
confidence: 99%
“…Other approaches could be possible as well. For example, we rigorously avoided the forcing function approach, but that approach has shown benefit in studies of medication safety prompting systems 24,25 even though it also leads to high override rates. 26 As another example, a recent Cochrane review 1 found that computer-generated reminders delivered on paper were effective in changing practice and that providing space for physicians to respond led to greater effect size; including an explanation of the reminder, however, which we avoided, also improved effect size.…”
Section: Discussionmentioning
confidence: 99%
“…CDSSs for medication management can have beneficial effects such as reduction in medication errors, but results are varying [16][17][18][19][20]. Effects of a CDSS can be related to factors such as implementation, design, and clinical relevance of alerts [10,[21][22][23][24][25]. An excessive amount of alerts can cause alert fatigue which may result in alert overrides, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…131 Qualitative methods such as simulations can provide insight into possible mechanisms of action of digital interventions, including factors to do with design and delivery, which can impact on uptake and engagement and, therefore, effectiveness. 262 Qualitative observation in practice can help to assess patterns of engagement and implementation and to discover unanticipated adverse effects of interventions. 169 …”
Section: Qualitative Process Evaluationsmentioning
confidence: 99%